Blocking heme oxygenase-1 by zinc protoporphyrin reduces tumor hypoxia-mediated VEGF release and inhibits tumor angiogenesis as a potential therapeutic agent against colorectal cancer. Issue 1 (December 2016) - Cheng, Chun-Chia; Guan, Siao-Syun; Yang, Hao-Jhih; Chang, Chun-Chao; Luo, Tsai-Yueh; Chang, Jungshan; Ho, Ai-Sheng
Abstract Background Hypoxia in tumor niche is one of important factors to start regeneration of blood vessels, leading to increase survival, proliferation, and invasion in cancer cells. Under hypoxia microenvironment, furthermore, steadily increasedhypoxia-inducible factor -1α (HIF-1α) is observed, and can increase vascular endothelial growth factor (VEGF) expression and promote angiogenesis. Zinc protoporphyrin (ZnPP), a heme oxygenase-1 (HO-1) inhibitor, is potential to inhibit tumor proliferation and progression. However, the mechanism of ZnPP in inhibition of tumor is not completely clear. We hypothesize that ZnPP may modulate HIF-1α through inhibiting HO-1, and then inhibit angiogenesis and tumor progression. This study aimed to dissect the mechanism of ZnPP in tumor suppression. Results We observed the amount of VEGF was increased in the sera of the colorectal cancer (CRC) patients (n  = 34, p  < 0.05). Furthermore, increased VEGF expression was also measured in colorectal cancer cells, HCT-15, culturing under mimicking hypoxic condition. It suggested that hypoxia induced VEGF production from cancer cells. VEGF production was significantly reduced from HCT-15 cells after exposure to HIF-1α inhibitor KC7F2, suggesting that HIF-1α regulated VEGF production. Moreover, we observed that the HO-1inhibitor ZnPP inhibited the expressions of HIF-1α and VEGF coupled with cell proliferations of HCT-15 cells, suggesting that ZnPP blocked HIF-1α expression, and then inhibited the consequent VEGF production. In the xenograft model, we also observed that the animals exposed to ZnPP displayed much smaller tumor nodules and less degree of angiogenesis with decreased expression of the angiogenesis marker, αvβ3 integrin, compared to that in normal control. Conclusions This study demonstrated that VEGF level in serum was elevated in the patients with CRC. The HO-1 inhibitor, ZnPP, possessed the properties of anti-tumor agent by decreasing HIF-1α levels, blocking VEGF production, impairing tumor angiogenesis, and inhibiting tumor growth.